Endovascular thrombectomy versus standard bridging thrombolytic with endovascular thrombectomy within 4·5 h of stroke onset: an open-label, blinded-endpoint, randomised non-inferiority trial. Issue 10346 (9th July 2022) - Mitchell, Peter J; Yan, Bernard; Churilov, Leonid; Dowling, Richard J; Bush, Steven J; Bivard, Andrew; Huo, Xiao Chuan; Wang, Guoqing; Zhang, Shi Yong; Ton, Mai Duy; Cordato, Dennis J; Kleinig, Timothy J; et al.
Summary: Background: The benefit of combined treatment with intravenous thrombolysis before endovascular thrombectomy in patients with acute ischaemic stroke caused by large vessel occlusion remains unclear. We hypothesised that the clinical outcomes of patients with stroke with large vessel occlusion treated with direct endovascular thrombectomy within 4·5 h would be non-inferior compared with the outcomes of those treated with standard bridging therapy (intravenous thrombolysis before endovascular thrombectomy). Methods: DIRECT-SAFE was an international, multicentre, prospective, randomised, open-label, blinded-endpoint trial. Adult patients with stroke and large vessel occlusion in the intracranial internal carotid artery, middle cerebral artery (M1 or M2), or basilar artery, confirmed by non-contrast CT and vascular imaging, and who presented within 4·5 h of stroke onset were recruited from 25 acute-care hospitals in Australia, New Zealand, China, and Vietnam. Eligible patients were randomly assigned (1:1) via a web-based, computer-generated randomisation procedure stratified by site of baseline arterial occlusion and by geographic region to direct endovascular thrombectomy or bridging therapy. Patients assigned to bridging therapy received intravenous thrombolytic (alteplase or tenecteplase) as per standard care at each site; endovascular thrombectomy was also per standard of care, using the Trevo device (Stryker Neurovascular, Fremont, CA, USA) as first-line intervention. Personnel assessing outcomes were masked to group allocation; patients and treating physicians were not. The primary efficacy endpoint was functional independence defined as modified Rankin Scale score 0–2 or return to baseline at 90 days, with a non-inferiority margin of –0·1, analysed by intention to treat (including all randomly assigned and consenting patients) and per protocol. The intention-to-treat population was included in the safety analyses. The trial is registered with ClinicalTrials.gov, NCT03494920, and is closed to new participants. Findings: Between June 2, 2018, and July 8, 2021, 295 patients were randomly assigned to direct endovascular thrombectomy (n=148) or bridging therapy (n=147). Functional independence occurred in 80 (55%) of 146 patients in the direct thrombectomy group and 89 (61%) of 147 patients in the bridging therapy group (intention-to-treat risk difference –0·051, two-sided 95% CI –0·160 to 0·059; per-protocol risk difference –0·062, two-sided 95% CI –0·173 to 0·049). Safety outcomes were similar between groups, with symptomatic intracerebral haemorrhage occurring in two (1%) of 146 patients in the direct group and one (1%) of 147 patients in the bridging group (adjusted odds ratio 1·70, 95% CI 0·22–13·04) and death in 22 (15%) of 146 patients in the direct group and 24 (16%) of 147 patients in the bridging group (adjusted odds ratio 0·92, 95% CI 0·46–1·84). Interpretation: We did not show non-inferiority of direct endovascular thrombectomy compared with bridging therapy. The additional information from our study should inform guidelines to recommend bridging therapy as standard treatment. Funding: Australian National Health and Medical Research Council and Stryker USA.